Increased knowledge about floral preservatives influences customers’ perception of the quality and value of a floral arrangement purchase - Jenkins, Morgan (Kansas State University, 2010)
Despite extensive evidence that appropriate use of floral preservatives extends postharvest longevity of most fresh flowers, their use by traditional full-service florists has been observed to be highly variable. This research was developed to determine if knowledge about floral preservatives increases consumers’ perception of quality, purchase intention, and price of a floral arrangement. A survey was administered to 222 participants at two locations in Manhattan, Kansas during April 2010. Seventy-three percent of respondents fell within the age range of Gen Y. The survey instrument contained four levels of presentation of a floral arrangement that were associated with increasing knowledge about the use of a floral preservative on consumers’ perceptions about the quality and price of that arrangement. Results were analyzed via within-subjects ANOVA, Bonferroni post-hoc tests, t-tests, and regression analyses. Participants of the survey rated the quality of a floral arrangement higher from Level 2 (presence of floral preservative not explicit) to 3 (presence of floral preservative explicit) and Level 3 to 4 (after reading 191 word count message about floral preservative function and effectiveness). Their intent to purchase the floral arrangement generally increased with each level of presentation. Participants increased the price that they were willing to pay for the floral arrangement at each level of presentation, starting at $25.49 at Level 1 (no floral preservative use indicated) to $29.17 at Level 4. Participants were more knowledgeable about the benefits of floral preservatives and believed that floral preservatives increased the value of floral arrangements after reading a message describing their function and effectiveness more so than before reading the message. Younger participants were more willing to pay more for floral arrangements with floral preservatives than older participants. As consumers become more aware of the use of floral preservatives and more knowledgeable about how and why they are effective, they attribute higher quality to floral arrangements with preservatives, are willing to pay more for arrangements with preservatives, and their purchase intention frequency increases. Florists should consider providing a message about the function and effectiveness of floral preservatives to their customers, and then market their use of these materials.
Keywords: Consumer preference; Floral preservative; Agriculture, General (0473)